Algoritmo de diseño de una planta mezcladora móvil de concreto en función del volumen de producción - Chuquillanqui Sevillano, Saúl Felipe (2019)
In the present thesis the study of mobile concrete mixers was carried out, trying to understand its operation and composition. Technical visits were made to some companies to check their concrete mixers and take data on their operation and technologies they use. After analyzing the different components and operation of the mixers, a bibliographic review of all the theoretical and technical information necessary related to its elements was made. The general information that was found was filtered, applied and delimited only for the purpose that this thesis implies. Finally, the calculation procedures were organized and the limitations and considerations for the correct design were established, using basic engineering calculation and in some cases the support of engineering software.